Perspective on Potential Clinical Applications of Recombinant Human Interleukin-7 - Sportès, Claude (Ann N Y Acad Sci, 2009)
Interleukin-7 has critical and nonredundant roles in T cell development, hematopoiesis, and postdevelopmental immune functions as a prototypic homeostatic cytokine. Based on a large body of preclinical evidence, it may have multiple therapeutic applications in immunodeficiency states, either physiologic (immuno-senescence), pathologic (HIV) or iatrogenic (postchemotherapy and posthematopoietic stem cell transplant) and may have roles in immune reconstitution or enhancement of immunotherapy. Early clinical development trials in humans show that, within a short time, rhIL-7 administration results in a marked preferential expansion of both naive and memory CD4 and CD8 T cell pools with a tendency toward enhanced CD8 expansion. As a result, lymphopenic or normal older hosts develop an expanded circulating T cell pool with a profile that resembles that seen earlier in life with increased T cell repertoire diversity. These results, along with a favorable toxicity profile, open a wide perspective of potential future clinical applications.